Cover Picture: Effects of heavy alkali elements in Cu(In, Ga)Se2 solar cells with efficiencies up to 22.6% (Phys. Status Solidi RRL 8/2016). Issue 8 (August 2016) - Jackson, Philip; Wuerz, Roland; Hariskos, Dimitrios; Lotter, Erwin; Witte, Wolfram; Powalla, Michael
Abstract : No abstract is available for this article. Abstract : The Centre for Solar Energy and Hydrogen Research Baden‐Württemberg (ZSW) has nudged up the performance bar for thin‐film solar cells yet another notch. The Stuttgart‐based scientists have achieved 22.6 percent efficiency with a Cu(In, Ga)Se2 (CIGS) solar cell. One of the major strategies used to achieve this milestone was the application of a post‐deposition treatment (PDT) on the CIGS absorber material with alkali elements. Initially this treatment was used by researchers to supply sodium to flexible CIGS devices in order to thereby boost the open circuit voltage. However, exchanging potassium for sodium brought yet another performance boost in the past three years. The Letter on pp.583–586 describes the impact even heavier alkali elements like rubidium and cesium have on CIGS device performance when applied with the same PDT procedure: another performance gain can be demonstrated. In addition, the observed effect on the device level is investigated on the atomic scale by secondary ion mass spectrometry (SIMS). A competitive interaction between light and heavy alkali elements is detected. With these results and analytical findings, CIGS once more proves to be a scientifically interesting and economically promising second generation PV technology for the near future.